Fancy Nancy : Every day is Earth Day - O'Connor, Jane.; Ivanov, A. (Aleksey); Ivanov, O. (Olga) (New York : HarperCollins, 2010)
When Nancy, the girl who loves to use fancy words, learns about Earth Day and "being green," her enthusiasm causes problems at home.
Keywords: Earth Day -- Juvenile fiction; Environmental protection -- Juvenile fiction; Families -- Juvenile fiction; Schools -- Juvenile fiction; Vocabulary -- Juvenile fiction